2011
DOI: 10.3109/14756366.2011.622272
|View full text |Cite
|
Sign up to set email alerts
|

BPTES inhibition of hGA124–551, a truncated form of human kidney-type glutaminase

Abstract: The initial transcript of the GLS1 gene undergoes alternative splicing to produce two glutaminase variants (KGA and GAC) that contain unique C-terminal sequences. A truncated form of human glutaminase (hGA(124-551)) that lacks either C-terminal sequence was expressed in E.Coli and purified. This construct exhibits a hyperbolic glutamine saturation profile (K(m) of 1.6 mM). BPTES, bis-2[5-phenylacetamido-1,2,4-thiadiazol-2-yl]ethylsulfide, functions as a potent uncompetitive inhibitor of this construct (K(i) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
3
43
2
1
Order By: Relevance
“…S1A) and a shift toward greater potency with increasing glutamine concentrations ( Supplementary Fig. S1C), consistent with previous reports (18,21). In contrast, CB-839 behaved as a primarily noncompetitive inhibitor impacting V max but with minimal effect on K m ( Supplementary Fig.…”
Section: Cb-839 Is a Potent And Selective Glutaminase Inhibitorsupporting
confidence: 80%
See 2 more Smart Citations
“…S1A) and a shift toward greater potency with increasing glutamine concentrations ( Supplementary Fig. S1C), consistent with previous reports (18,21). In contrast, CB-839 behaved as a primarily noncompetitive inhibitor impacting V max but with minimal effect on K m ( Supplementary Fig.…”
Section: Cb-839 Is a Potent And Selective Glutaminase Inhibitorsupporting
confidence: 80%
“…The small-molecule BPTES was previously described as an allosteric glutaminase inhibitor active against both splice variants of the GLS gene, GAC and KGA (reported Ki between 0.2 and 3 mmol/L), but not the liver form of glutaminase, encoded by the GLS2 gene (18,19,21,22). CB-839 (Fig.…”
Section: Cb-839 Is a Potent And Selective Glutaminase Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition NHE mediated acid extrusion is up-regulated in cancer cells [19,20] importing a Na + load requiring Na+/K+ ATPase -ATP expenditure and ATP regeneration associated with acidogenic aerobic glycolysis(Warburg effect) and by substrate level phosphorylation. Because PIG (GGT/GGTP), NHE, glutamine transporter and glutaminase activities are all up-regulated in rapidly growing tumors, tagging molecular target inhibitors [21][22][23][24] with a ϒ-glutamyl moiety offers a tumor specific vehicle specific for limiting anaplerosis and preventing elevated cell pH, prerequisites for rapid tumor growth. …”
Section: Glutamate Is Generated By Extra-and Intracellular Glutaminasesmentioning
confidence: 99%
“…6.7 , one primitive test of this concept involves BPTES [bis-2-(5 phenylacetamido-1, 2, 4-thiadiazol-2-yl) ethyl sulfi de]. This uncompetitive inhibitor has been elucidated to inhibit human glutaminase [ 12 ]. Studies have revealed that BPTES, a small molecule, binds to an allosteric site at the dimer interface of KGA-a kidney-type glutaminase isoform (GLS1)-and leads to a conformational change near the catalytic site, which inactivates the enzyme [ 13 ].…”
Section: Glutamine Metabolism As a Target For Cancer Therapymentioning
confidence: 99%